Estrogen and DPP-4 inhibitor share similar efficacy in reducing brain pathology caused by cardiac ischemia-reperfusion injury in both lean and obese estrogen-deprived rats - Wasana Pratchayasakul (2018)
© 2017 by The North American Menopause Society. Objective: Cardiac ischemia-reperfusion injury (I/R) caused an oxidative burst, increased beta-amyloid production, and decreased dendritic spine density in the brain. However, the effect of cardiac I/R in the brain of estrogen-deprived rats who were or were not obese have not been investigated. Moreover, the benefits of estrogen or dipeptidyl peptidase-4 (DDP-4) inhibitor therapies in those conditions have never been determined. We hypothesized that cardiac I/R aggravates brain pathology in estrogen-deprived obese rats, to a greater extent when compared with estrogen-deprived lean rats, and treatment with either estrogen or a DPP-4 inhibitor attenuates those adverse effects. Methods: In protocol 1, rats were divided into sham operation (n = 12) or ovariectomy (n = 24). Sham-operated rats were fed with normal diet (ND) and ovariectomized rats were fed with either ND or high-fat diet (HF) for 12 weeks. Then, rats were subdivided to sham operation or cardiac I/R injury. In protocol 2, ovariectomized rats were given either ND (n = 18) or HF (n = 18). At week 13, ovariectomized rats were subdivided to receive vehicle, estradiol, or DPP-4 inhibitor for 4 weeks. Then, all rats were subjected to cardiac I/R. Results: Cardiac I/R injury aggravated brain oxidative stress, beta-amyloid production, and decreased dendritic spine density in either sham-operated or ovariectomized ND-fed rats, but not in ovariectomized HF-fed rats. Either estrogen or DPP-4 inhibitor therapies reduced those conditions in all rats with cardiac I/R. Conclusions: Cardiac I/R aggravates brain toxicity in estrogen-deprived lean rats, but not in the estrogen-deprived obese rats. Estrogen and DPP-4 inhibitor treatments attenuate those effects in all groups.